Platelets from glioblastoma patients promote angiogenesis of tumor endothelial cells and exhibit increased VEGF content and release - Clara Di Vito; Stefania Elena Navone; Giovanni Marfia; Loubna Abdel Hadi; Maria Elisa Mancuso; Alessandro Pecci; Francesco Maria Crisà; Valeria Berno; Paolo Rampini; Rolando Campanella; Laura Riboni (Platelets, 2017)
Glioblastoma multiforme (GBM) is the most common and fatal intracranial cancer in humans and exhibits intense and aberrant angiogenesis that sustains its malignancy and involves several angiogenic signals. Among them, vascular endothelial growth factor (VEGF) plays a key role and is overexpressed in GBM. Different cells appear to act as triggers of the aberrant angiogenesis, and, among them, platelets act as key participants. In order to provide further insights into the platelet features and angiogenic role in GBM, this study investigated the effects of platelet releasate on GBM-derived endothelial cells (GECs) and the levels of VEGF and endostatin, as pro- and anti-angiogenic components of platelet releasate from GBM patients. We demonstrate for the first time that: 1) platelet releasate exerts powerful pro-angiogenic effect on GECs, suggesting it might exert a role in the aberrant angiogenesis of GBM; 2) ADP and thrombin stimulation leads to significantly higher level of VEGF, but not of endostatin, in the releasate of platelets from GBM patients than those from healthy subjects; and 3) the intraplatelet concentrations of VEGF were significantly elevated in GBM patients as compared to controls. Moreover, we found a direct correlation between platelet-released VEGF and overall survival in our patient cohort. Although preliminary, these findings prompt further investigations to clarify the biologic relevance of platelet VEGF in GBM and prospective studies for screening GBM patients for anti-VEGF therapy and/or to optimize this treatment.